1997
DOI: 10.1073/pnas.94.4.1160
|View full text |Cite
|
Sign up to set email alerts
|

Novel pyridinium surfactants for efficient, nontoxic in vitro gene delivery

Abstract: Novel, double-chained pyridinium compounds have been developed that display highly efficient DNA transfection properties. The transfection efficiency of several of these compounds is enhanced by an order of magnitude, when compared with the transfection efficiency accomplished with the widely used cationic lipid system, lipofectin. Most importantly, the pyridinium compounds were found to be essentially nontoxic toward cells. Using various reporter genes, such as ␤-galactosidase and pNEO (a gene construct that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
159
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 25 publications
9
159
0
Order By: Relevance
“…Canine cav-1 was cloned in the PCDNA3 plasmid. Cells were transfected with the cationic lipid SAINT-2, according to a procedure previously described by van der Woude et al (1997). Briefly, cells were seeded in 35-mm dishes at low density, and the transfection was performed the following day.…”
Section: Constructs Transfection and Clonal Selectionmentioning
confidence: 99%
“…Canine cav-1 was cloned in the PCDNA3 plasmid. Cells were transfected with the cationic lipid SAINT-2, according to a procedure previously described by van der Woude et al (1997). Briefly, cells were seeded in 35-mm dishes at low density, and the transfection was performed the following day.…”
Section: Constructs Transfection and Clonal Selectionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] There has been considerable interest in characterizing the nature of the fundamental interactions between cationic agents and DNA, and several general approaches have been designed to unravel such interactions. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] One of the important driving forces in all of these systems is the long-range electrostatic interaction between molecules of opposite charge.…”
Section: Introductionmentioning
confidence: 99%
“…As has been recently shown, cholesterol depletion, as accomplished in this manner, results in the inhibition of clathrin-mediated endocytosis, whereas nonclathrin-mediated endocytosis is much less affected. It was demonstrated that the decrease in clathrin-mediated endocytosis is caused by the disability of coated pits to invaginate and detach from the plasma membrane (17,18).Here, we have determined the transfection efficiency of COS7 cells, using lipoplexes composed of the cationic amphiphile SAINT-2 and dioleoylphosphatidylethanolamine (DOPE) (5,19,20), following depletion of plasma membrane cholesterol with M␤CD. Because M␤CD treatment of cells, next to an interference of coated pit organization, may potentially interfere with the internalization via caveolae as well, the effect of two additional drugs, filipin III and chlorpromazine, were tested to differentiate between the involvement of either type of endocytosis (non-coated pit (caveolae) versus coated pit (clathrindependent)).…”
mentioning
confidence: 99%
“…Here, we have determined the transfection efficiency of COS7 cells, using lipoplexes composed of the cationic amphiphile SAINT-2 and dioleoylphosphatidylethanolamine (DOPE) (5,19,20), following depletion of plasma membrane cholesterol with M␤CD. Because M␤CD treatment of cells, next to an interference of coated pit organization, may potentially interfere with the internalization via caveolae as well, the effect of two additional drugs, filipin III and chlorpromazine, were tested to differentiate between the involvement of either type of endocytosis (non-coated pit (caveolae) versus coated pit (clathrindependent)).…”
mentioning
confidence: 99%